M187. A MULTIMODAL, NEUROIMAGING STUDY OF TDCS MECHANISMS RELATED TO AUDITORY VERBAL HALLUCINATIONS IN HEALTHY INDIVIDUALS. (18th May 2020) - Lynn, Marquardt; Kusztrits, Isabella; Craven, Alexander R; Hugdahl, Kenneth; Specht, Karsten; Hirnstein, Marco
Abstract: Background: Transcranial direct current stimulation (tDCS) is a brain stimulation method which is growing in popularity in both research and clinical settings, especially as a treatment of auditory verbal hallucinations (AVH) in patients with schizophrenia. However, the underlying neural mechanisms of this tDCS treatment are poorly understood. Current AVH models propose that AVH arise from hyperactivation in the left temporo parietal (LTPC), causing AVH, and from hypoactivation in the left dorsolateral prefrontal cortex (LDLPFC), leading to diminished control over AVH. We aimed to "mimic" this hyper-/hypoactivation pattern in healthy individuals with tDCS by placing the excitatory anode above the LTPC and the inhibitory cathode over the LDLPFC and then to study the effects of tDCS on these brain areas. Previous studies examined either brain activation, neurochemistry, or behavior, with other electrode montages, but few looked at those aspects together. The present study therefore examined tDCS effects with fMRI (functional magnetic resonance imaging), MR spectroscopy, behavioral tasks and simulation of the electric field in a multimodal approach. We hypothesized that tDCS would (a) lead to similar behavioral deficits in healthy individuals as in schizophrenia patients and (b) induce changes in the stimulated areas on neurotransmitter and functional activation level. Methods: Thirty-two healthy participants (18 males, mean age=26 yrs) were tested twice, ca. one week apart, with either real or sham (control) 2mA tDCS for 20 min while in a GE 750, 3T MRI scanner. The order of real/sham stimulation was counterbalanced in a double-blind design. During fMRI, participants completed a dichotic listening task in a block design, in order to measure behavior and brain activation changes. Before and after fMRI/tDCS, MR spectroscopy was carried out in two voxels placed under the electrodes. The data was analyzed with repeated measures ANOVAs. After data-collection, the structural T1 sequence was used to simulate the electric field of tDCS stimulation. Results: Glx (Glutamate and glutamine combined) showed a trend (F(1, 31)=3.35, p=.077, η2p=.098) to increase after tDCS stimulation compared to before, however this was not electrode specific. Neither fMRI, nor the dichotic listening task (all F≤1.64, p≥.203, η2p≤.052) showed any stimulation specific differences between real and sham stimulation. The tDCS simulation revealed large individual differences in the electric field induced. Discussion: In the present study, tDCS seemed to have little effect on the measured brain parameters and little validation for the AVH model was found. The mechanisms of tDCS and how it affects the underlying brain tissue are poorly understood and seem to be affected by different stimulation parameters like stimulation duration, current strength and electrode montage. To use tDCS most effectively in schizophrenia research and treatment of auditory hallucinations, it should be validated with a multitude of methods, similar to the approach described here.